STRATEGI KOMUNIKASI DINAS PARIWISATA DALAM PENGEMBANGAN DANAU MATANO SEBAGAI DESTINASI WISATA DI KECAMATAN NUHA KABUPATEN LUWU TIMUR - Nirvana , Nirvana; Ahdan, Ahdan (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
The purpose of this study was to examine the Communication Strategy of the Tourism Office and the Concept of Tourism Destination Development. This study used a qualitative descriptive method, with five (5) informants in this study. The data collection technique was through observation, interviews and documentation. The results of this study indicate that the communication strategy carried out by the Tourism Office in the development of Lake Matano is to inform the public through social media or directly to the community to be involved in the development of Lake Matano. The concept of developing Lake Matano is to make Lake Matano a geogical park or geo park because Lake Matano is the deepest lake in Southeast Asia.